The Glass Cliff: Exploring the Dynamics Around the Appointment of Women to Precarious Leadership Positions in Corporate South Africa - Mashele, Winsome (University of the Witwatersrand, Johannesburg, 2021)
The current research explores the "glass cliff" form of discrimination. The research argues that while women are now appointed in high-profile positions, there is a greater likelihood that they end up on a 'glass cliff' as compared to their male counterparts. Glass cliff positions put women executives' in potentially risky roles that could harm their reputations and career prospects because, when a company performs poorly, people tend to blame its leadership without considering situational variables. The research problem statement centres around the overrepresentation of women who are in senior leadership positions in organizations that are experiencing difficulties, which is an increasing concern in corporate South Africa. The main objectives of the study, among others includes to: (i) gain a better understanding of why women choose risky leadership positions. (ii) identify the leadership experiences of women in leading organisations in relation to gender. (iii) understand the suitable leadership styles that women facing the glass cliff have at their disposal to build relationships with internal shareholders as well as influence the structure of the organisation. (iv) understand the tools and resources that are needed to support women in senior leadership roles during times of crises in corporate South Africa. Design/methodology/approach: A qualitative research methodology was employed, and data collected through semi-structured interviews from a total of 15 participants. Findings: The findings suggest that women are now allowed to occupy senior leadership positions where these positions record a decline in status, competence and prestige, and as a result are time consuming and difficult to combine with a successful academic career. An important set of findings is: (i) the participants perceived the risky activity as a form of promotional opportunity and were willing to accept an offer. (ii) if women are placed in the right positions with the right skills, success is potentially guaranteed. (iii) leaders should practice the situational leadership style which evolves according to the situation, the time at hand and its nature. Contribution / value: Despite some limitations that were experienced over the course of the study, some answers emerged in response to the key question on which the study was premised. Furthermore, the aim of this study was achieved in terms of its contribution not only in providing guidance to organizational decision makers, policy makers and business leaders to address inequalities in corporate South Africa, but also in highlighting the role played by women in making career decisions within the rubric of the glass cliff phenomenon
A research report submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2021
Keywords: Gender; Leadership positions; Glass cliff; Corporate; Risk taking; Precarious; South Africa; UCTD; SDG-5: Gender equality